Effect of Age-at-Harvest on Sugarcane (Saccharum officinarum L.) Yields in Southwestern Nigeria - Ogunremi, E. A. (Faculty of Agriculture, University of Ife, 2015)
The experiment testing the effect of age-at-harvest on sugarcane showed that standing-over significantly reduced cane and sugar yields. Highest yields were obtained from 15 month-old crops. Standing-over reduced yields by increasing the percentage of unmillable cane stalks. The need to develop suitable and more adaptable cultivars is highlighted.